Financial Market of Europe in Displaying the Dynamics of Prices for Shares of Major European Companies - Lyashenko, Vyacheslav; Stepanenko, Nataliia; Osypova, Svitlana (My University, 2022)
The financial market plays an important role in the implementation and development of economic relations between various business entities, the functioning of a market economy. This is due to the fact that the financial market is one of the key elements of the financial system. Therefore, a comprehensive analysis of the functioning of various segments of the financial market is important. One of the parameters for determining such segmentation of the financial market is the territorial affiliation of the relevant market segment. Based on this, we consider the European financial market. To analyze the European financial market, we consider its main indicators and the dynamics of prices for shares of major European companies. The paper also considers the issue of analyzing the mutual dynamics of prices for shares of major European companies. For such an analysis, we use the wavelet ideology. We use wavelet coherence estimates as a method for mutual analysis of relevant data. The paper presents a lot of empirical and statistical material in the form of relevant graphs and diagrams. This allows you to understand the logic of the study and the results obtained.
Keywords: price; stock; financial market; business entities; stock indices; market segments; wavelet analysis; wavelet coherence